2013
DOI: 10.1242/dmm.010447
|View full text |Cite
|
Sign up to set email alerts
|

Moderate and high amounts of tamoxifen in α-MHC-MerCreMer mice induce a DNA damage response, leading to heart failure and death

Abstract: SUMMARYNumerous mouse models have utilized Cre-loxP technology to modify gene expression. Adverse effects of Cre recombinase activity have been reported, including in the heart. However, the mechanisms associated with cardiac Cre toxicity are largely unknown. Here, we show that expression of Cre in cardiomyocytes induces a DNA damage response, resulting in cardiomyocyte apoptosis, cardiac fibrosis and cardiac dysfunction. In an effort to increase the recombination efficiency of a widely used tamoxifen-sensitiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
127
4

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 132 publications
(143 citation statements)
references
References 42 publications
(82 reference statements)
10
127
4
Order By: Relevance
“…We used moderate amounts of tamoxifen (35 mg/kg/day) as many other laboratories described previously. [44][45][46] In this dose of tamoxifen, its cardiac toxicity was minimal as reported by Bersell et al 42 Indeed, we observed a small but significant adverse effect of tamoxifen injection on cardiac ejection fraction of WT mice (Figure 8e). However, compared with Gab1-WT mice treated with tamoxifen, we found that Gab1-icKO mice treated with tamoxifen had much greater reduction of cardiac function (Figure 8e), and this could be because of intrinsic defects of cardiac function in Gab1-icKO mice or the intolerance of Gab1-icKO mice to mild tamoxifen cardiac toxicity.…”
Section: Resultssupporting
confidence: 82%
See 1 more Smart Citation
“…We used moderate amounts of tamoxifen (35 mg/kg/day) as many other laboratories described previously. [44][45][46] In this dose of tamoxifen, its cardiac toxicity was minimal as reported by Bersell et al 42 Indeed, we observed a small but significant adverse effect of tamoxifen injection on cardiac ejection fraction of WT mice (Figure 8e). However, compared with Gab1-WT mice treated with tamoxifen, we found that Gab1-icKO mice treated with tamoxifen had much greater reduction of cardiac function (Figure 8e), and this could be because of intrinsic defects of cardiac function in Gab1-icKO mice or the intolerance of Gab1-icKO mice to mild tamoxifen cardiac toxicity.…”
Section: Resultssupporting
confidence: 82%
“…These results suggest that Gab1 deficiency in adult mice impairs cardiac function and potentially increased sensitivity to mild tamoxifen toxicity. 41,42 Discussion…”
Section: Resultsmentioning
confidence: 99%
“…7H). These results indicate that the hypertrophic effect was caused by tamoxifen and Creinduced expression of the SA mutation in cardiomyocytes rather than by cardiac toxicity of tamoxifen-induced Cre activity in cardiomyocytes, as has been observed previously with higher doses of tamoxifen (35). Evidently, the SA mutation is sufficient to impair cardiovascular homeostasis and cause cardiac hypertrophy within 4 wk when expressed only in cardiomyocytes.…”
Section: Cardiomyocyte-specific Expression Of the Sa Mutation Leads Tosupporting
confidence: 79%
“…To induce αMHC-MerCreMer activation, mice were injected i.p. with tamoxifen (T5648; Sigma) once a day at 30 mg·kg −1 ·d −1 for three consecutive days (35). All mice used in this study were pathogen free and were housed in the University of Washington Animal Facility at constant temperature (22°C), on 12-h light/12-h dark cycles, with ad libitum access to food and water.…”
Section: Methodsmentioning
confidence: 99%
“…It should be noted that high doses of tamoxifen in combination with merCremer (mCrem, a modified tamoxifen inducible Cre construct) may cause focal cardiac fibrosis in a strain dependent manner [35]. Additionally, there are several reports that indicate that Cre expression itself can be cytotoxic, and appropriate controls for monitoring this issue should be established [36-39]. …”
Section: Fibroblast Definitionmentioning
confidence: 99%